Hazardous industrial waste treatment - Wang, Lawrence K. (CRC/Taylor & Francis, 2007)
Presenting chapters from the bestselling "Handbook of Industrial and Hazardous Wastes Treatment, Second Edition", this resource features valuable strategies culled from the latest technologies and keen insights of experts in the field. "Hazardous Industrial Waste Treatment" explains industry and waste-specific analyses and treatment methods for industrial and hazardous waste materials - from explosive wastes to landfill leachate to wastes produced by pharmaceutical and food industries. Additional information covers the means of monitoring waste on site, pollution, and site remediation, and includes a timely evaluation of the role of biotechnology in contemporary industrial waste management